A Shortcut Method to Predict Particle Size Changes during Char Combustion and Gasification under regime II Conditions. Issue 2 (25th January 2022) - Kreitzberg, Thobias; Phounglamcheik, Aekjuthon; Haugen, Nils Erland L.; Kneer, Reinhold; Umeki, Kentaro
ABSTRACT: In most industrial applications, combustion and gasification of char progresses under regime II conditions. Unlike in other regimes, both particle size and density change simultaneously in regime II due to non-uniform consumption of carbon inside the particles. In this work, mathematical predictions of diameter changes in regime II were made by a one-dimensional simulation tool, where transient species balances are resolved locally inside the particle. This simulation is computationally expensive and usually not appropriate for the implementation in comprehensive CFD simulations of combustion or gasification processes. To overcome this restraint, an alternative shortcut method with affordable computation time has been developed and validated against the detailed model. This method allows the calculation of diameter changes during combustion and gasification from precalculated effectiveness factors. Additionally, the change of particle size has been investigated experimentally in a single particle converter setup. Therein, particles are fixed on a sample holder placed in the hot flue gas of a flat flame burner. Size and temperature trends are optically assessed by a 3CCD camera.